Sucrose Phosphate Synthase Activity Rises in Correlation with High-Rate Cellulose Synthesis in Three Heterotrophic Systems - Babb, V. Michelle (American Society of Plant Physiologists, 2001)
Based on work with cotton fibers, a particulate form of sucrose (Suc) synthase was proposed to support secondary wall cellulose synthesis by degrading Suc to fructose and UDP-glucose. The model proposed that UDP-glucose was then channeled to cellulose synthase in the plasma membrane, and it implies that Suc availability in cellulose sink cells would affect the rate of cellulose synthesis. Therefore, if cellulose sink cells could synthesize Suc and/or had the capacity to recycle the fructose released by Suc synthase back to Suc, cellulose synthesis might be supported. The capacity of cellulose sink cells to synthesize Suc was tested by analyzing the Suc phosphate synthase (SPS) activity of three heterotrophic systems with cellulose-rich secondary walls. SPS is a primary regulator of the Suc synthesis rate in leaves and some Suc-storing, heterotrophic organs, but its activity has not been previously correlated with cellulose synthesis. Two systems analyzed, cultured mesophyll cells of Zinnia elegans L. var. Envy and etiolated hypocotyls of kidney beans (Phaseolus vulgaris), contained differentiating tracheary elements. Cotton (Gossypium hirsutum L. cv Acala SJ-1) fibers were also analyzed during primary and secondary wall synthesis. SPS activity rose in all three systems during periods of maximum cellulose deposition within secondary walls. The Z. elegans culture system was manipulated to establish a tight linkage between the timing of tracheary element differentiation and rising SPS activity and to show that SPS activity did not depend on the availability of starch for degradation. The significance of these findings in regard to directing metabolic flux toward cellulose will be discussed.